فعالية استخدام وسيلة الكلمات المتقاطعة في تدريبات مهارة القراءة لطلاب المدرسة الثانوية الإسلامية الحكومية الواحدة فروبولينجو - Qurrota A'yun, Nissa Aulia (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2023)
ABSTRACT In this research, researchers used crossword puzzle media in reading skills training for class X MAN 1 Probolinggo City. This research aims (1) To find out how qualified the application of crossword puzzle media reading skills to MAN 1 Probolinggo City students is (2) To find out how effective the use of crossword puzzles is in training reading skills to students in MAN 1 Probolinggo City. The research method used in this study is to use an experimental method. The results of the research obtained are: that Crossword Puzzle Media is effectively used in learning Arabic, especially in improving students' reading skills. The average score of students' reading skills exam results in the control group was only 72,7 and in the experimental group of 85,15 with a significance of 0. 000 which means that there is a difference in the effectiveness of conventional learning media with the effectiveness of Crossword Media learning media in improving reading skills ability. So, it can be concluded that there is a significant difference from the average pre-test and post-test so that Crossword Media is effectively used when learning Arabic to improve the reading skills students of MAN 1 Probolinggo City. Keywords: Crossword Media, Reading Skills, Arabic Learning ملخص في هذه البحث، أخذت الباحثة باستخدام وسيلة الكلمات المتقاطعة في تدريبات مهارة القراءة للفصل العاشر في المدرسة الثانوية الإسلامية الحكومية الواحدة فروبولينجو. تهدف هذه الدراسة إلى (1) لمعرفة مدى تطبيق مهارات قراءة الكلمات المتقاطعة على طلاب في المدرسة الثانوية الإسلامية الحكومية الواحدة فروبولينجو, (2) لمعرفة مدى فعالية استخدام الألغاز المتقاطعة في تدريب مهارات القراءة للطلاب في في المدرسة الثانوية الإسلامية الحكومية الواحدة فروبولينجو . طريقة البحث المستخدمة في هذا البحث هي استخدام المنهج التجريبي. نتائج البحث التي تم الحصول عليها هي: أن وسيلة الكلمات المتقاطعة تستخدم بشكل فعال في تعلم اللغة العربية وخاصة في تحسين مهارات القراءة لدى الطلاب. كان متوسط ​​درجات نتائج اختبار مهارات القراءة لدى الطلاب في المجموعة الضابطة 72.7 فقط وفي المجموعة التجريبية 85.15 مع دلالة 0.000، مما يعني أن هناك اختلافًا في فعالية وسائط التعلم التقليدية مع وسائط التعلم التقليدية. فعالية وسائط تعليم الكلمات المتقاطعة في تحسين مهارات القراءة. لذلك يمكن أن نستنتج أن هناك فرقًا كبيرًا في متوسط ​​الاختبار القبلي والبعدي بحيث يتم استخدام وسيلة الكلمات المتقاطعة بشكل فعال في تعلم اللغة العربية لتحسين القدرة على القراءة لدى طلاب في المدرسة الثانوية الإسلامية الحكومية الواحدة فروبولينجو. الكلمات المفتاحية: وسيلة الكلمات المتقاطعة, مهارة القراءة, تعليم اللغة العربية